2022
DOI: 10.1007/s00403-022-02446-9
|View full text |Cite|
|
Sign up to set email alerts
|

Microneedling combined with botulinum toxin-A versus microneedling combined with platelet-rich plasma in treatment of atrophic acne scars: a comparative split face study

Abstract: Background Atrophic post-acne scarring constitutes a troublesome cosmetic concern for both patients and dermatologists. Old and new therapies as well as combinations are being introduced to achieve a satisfactory response. Microneedling has been used either alone or under different combinations for its treatment. The aim was to compare its combination with topical platelet-rich plasma versus its combination with topical Botulinum Toxin-A. Methods 30 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“… 19 , 20 , 21 , 22 , 23 In a study by Waleed Albalat et al which compared effectiveness of microneedling combined with botulinum toxin‐A versus microneedling combined with platelet‐rich plasma in treatment of atrophic acne scars, the results showed that there was no significant difference between two methods in the treatment of atrophic acne scars and Both combinations are effective options for treating acne scars. 24 Another study by Sahar A. Ismail which compared the microneedling alone or platelet rich plasma alone or combined both therapeutic in the treatment of atrophic acne scars, their results showed that the skin microneedling, PRP and combined microneedling with PRP are effective therapeutic approaches in atrophic post‐acne scars treatment. However, combined microneedling with PRP had better outcomes in all subgroups of atrophic acne scars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 , 20 , 21 , 22 , 23 In a study by Waleed Albalat et al which compared effectiveness of microneedling combined with botulinum toxin‐A versus microneedling combined with platelet‐rich plasma in treatment of atrophic acne scars, the results showed that there was no significant difference between two methods in the treatment of atrophic acne scars and Both combinations are effective options for treating acne scars. 24 Another study by Sahar A. Ismail which compared the microneedling alone or platelet rich plasma alone or combined both therapeutic in the treatment of atrophic acne scars, their results showed that the skin microneedling, PRP and combined microneedling with PRP are effective therapeutic approaches in atrophic post‐acne scars treatment. However, combined microneedling with PRP had better outcomes in all subgroups of atrophic acne scars.…”
Section: Discussionmentioning
confidence: 99%
“…There were several studies that compare efficacy of different treatment methods in the atrophic acne scars 19–23 . In a study by Waleed Albalat et al which compared effectiveness of microneedling combined with botulinum toxin‐A versus microneedling combined with platelet‐rich plasma in treatment of atrophic acne scars, the results showed that there was no significant difference between two methods in the treatment of atrophic acne scars and Both combinations are effective options for treating acne scars 24 . Another study by Sahar A. Ismail which compared the microneedling alone or platelet rich plasma alone or combined both therapeutic in the treatment of atrophic acne scars, their results showed that the skin microneedling, PRP and combined microneedling with PRP are effective therapeutic approaches in atrophic post‐acne scars treatment.…”
Section: Discussionmentioning
confidence: 99%